2015
DOI: 10.2215/cjn.10101014
|View full text |Cite
|
Sign up to set email alerts
|

Change in Multiple Filtration Markers and Subsequent Risk of Cardiovascular Disease and Mortality

Abstract: Background and objectives Kidney disease progression, assessed by change in eGFR on the basis of creatinine, is an independent risk factor for cardiovascular disease and death. This study aimed to evaluate whether changes in multiple filtration markers, individually and combined, were associated with cardiovascular disease and death.Design, setting, participants, & measurements Creatinine, cystatin C, and b 2 -microglobulin were measured among 9716 Atherosclerosis Risk in Communities Study participants in 1990… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
17
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 17 publications
(18 citation statements)
references
References 42 publications
0
17
1
Order By: Relevance
“…AKI in survivors of critical illness predicts a worse frailty status after discharge [17]. The presence of AKI is also strongly associated with the risk of CVDs and death in critically ill patients [18]. Our study also revealed that patients with HS had a higher incidence of CKD during the follow-up period.…”
Section: Discussionmentioning
confidence: 52%
“…AKI in survivors of critical illness predicts a worse frailty status after discharge [17]. The presence of AKI is also strongly associated with the risk of CVDs and death in critically ill patients [18]. Our study also revealed that patients with HS had a higher incidence of CKD during the follow-up period.…”
Section: Discussionmentioning
confidence: 52%
“…Machine learning methods, and RF particularly, have been used before for CVD risk prediction. 1827 In this study, we were able to use deeply phenotyped data to predict outcomes in a population study that accounts for time to event. 28 The added advantage is that these methods can be extended and refined, regularly, with new data.…”
Section: Discussionmentioning
confidence: 99%
“…Based on results from prior studies, 22,23 we assessed change in eGFR in five categories (substantial decline [>30% decline], moderate decline [10%-30% decline], stable [± < 10%], moderate increase [10%-30% increase], substantial increase [>30% increase], with ± < 10% as the reference category) and the primary outcome. 22,23 For this categorical exposure, we only examined the combined outcome of major macrovascular and microvascular events, because the number of events in each cell was too small. We additionally adjusted for body mass index (BMI), total cholesterol, high-density lipoprotein (HDL) cholesterol, and smoking status in the fully adjusted models.…”
Section: Statistical Analysesmentioning
confidence: 99%
“…[16][17][18][19][20][21] Recently, several studies have reported that >30% change in alternative filtration markers alone and in combination with creatinine is associated with a strong risk of CKD progression in CKD populations, those at high risk of CKD, and the general population. 17,22,23 However, there have been limited data on alternative kidney filtration markers and health outcomes in individuals with type 2 diabetes. Studies have shown that a single measurement of cystatin C-based eGFR is associated with adverse outcomes in those with diabetes, but associations with B2M were reported only in studies of modest sample sizes or with a specific race/ethnic group.…”
Section: Introductionmentioning
confidence: 99%